2017
DOI: 10.3892/mmr.2017.6330
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of bone marrow mesenchymal stem cells on hepatitis B virus in vitro

Abstract: The aim of the present study was to explore the effects of co-culturing bone marrow-derived mesenchymal stem cells (BM-MSCs) cultured with hepatitis B virus (HBV)-infected lymphocytes in vitro. BM-MSCs and lymphocytes from Brown Norway rats were obtained from the bone marrow and spleen, respectively. Rats were divided into the following five experimental groups: Group 1, splenic lymphocytes (SLCs); group 2, HepG2.2.15 cells; group 3, BM-MSCs + HepG2.2.15 cells; group 4, SLCs + HepG2.2.15 cells; and group 5, SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…It has been confirmed that through the STAT3 pathway, IL-22 stimulates the proliferation of liver stem/progenitor cells (LPCs), cells participating in liver inflammatory responses [ 86 ]. Moreover, IL-22 production in hepatitis B patients is positively related to the HBV load [ 87 ]. By increasing CXCL9 and CXCL10 expression on hepatic stellate cells (HSCs), IL-22 also promotes inflammatory cell accumulation in the liver, leading to increased liver damage and hepatic fibrosis [ 88 ].…”
Section: Th22 Cells In Infectious Diseasesmentioning
confidence: 99%
“…It has been confirmed that through the STAT3 pathway, IL-22 stimulates the proliferation of liver stem/progenitor cells (LPCs), cells participating in liver inflammatory responses [ 86 ]. Moreover, IL-22 production in hepatitis B patients is positively related to the HBV load [ 87 ]. By increasing CXCL9 and CXCL10 expression on hepatic stellate cells (HSCs), IL-22 also promotes inflammatory cell accumulation in the liver, leading to increased liver damage and hepatic fibrosis [ 88 ].…”
Section: Th22 Cells In Infectious Diseasesmentioning
confidence: 99%
“…Current evidence presents IL-22 as a double-edge sword in HBV infection. Studies support that serum concentration of IL-22 is elevated in CHB [57][58][59][60], and so is the Th17 cells' percentage in peripheral blood [58]. In mice, Feng et al showed that CD3+ Tcells induce liver progenitor cell proliferation via IL-22 expression [61], while Park et al demonstrated that IL-22 secretion may be a protective mechanism in preventing further liver injury, despite its positive association with serum ALT levels [62].…”
Section: Interleukin-22mentioning
confidence: 99%
“…However, MSCs can enhance host cellular response against both HBV and HCV in vitro. Human MSCs suppressed HBV replication in hepatoblastoma cells when cocultured with splenic lymphocytes and reduced HCV replication in epithelial cells (220,221).…”
Section: Preclinical Models Of Viral Infectionmentioning
confidence: 99%